1998
DOI: 10.1074/jbc.273.47.30879
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the 11,14,15- and 11,12,15-Trihydroxyeicosatrienoic Acids as Endothelium-derived Relaxing Factors of Rabbit Aorta

Abstract: A number of endothelium-derived relaxing factors have been identified including nitric oxide, prostacyclin, and the epoxyeicosatrienoic acids. Previous work showed that in rabbit aortic endothelial cells, arachidonic acid was metabolized by a lipoxygenase to vasodilatory eicosanoids. The identity was determined by the present study. Aortic homogenates were incubated in the presence of [U-14 C]arachidonic acid, [U-14 C]arachidonic acid plus 15-lipoxygenase (soybean lipoxidase), or [U-14 C]15-hydroxyeicosatetrae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
154
1

Year Published

2004
2004
2010
2010

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 82 publications
(161 citation statements)
references
References 28 publications
6
154
1
Order By: Relevance
“…In rabbit aortas, ACh elicits synthesis of prostaglandins (26) and other AA metabolites (40) by activating muscarinic receptors (25). We reported that AA metabolites of 15-LO pathways, specifically 11,12,15-THETA and 15-H-11,12-EETA, mediate these L-NNA-and indomethacin-resistant vasorelaxations through opening apamin-sensitive K ϩ channels (11,23,42). The studies suggest that THETA and HEETA serve as EDHFs in rabbit aorta.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…In rabbit aortas, ACh elicits synthesis of prostaglandins (26) and other AA metabolites (40) by activating muscarinic receptors (25). We reported that AA metabolites of 15-LO pathways, specifically 11,12,15-THETA and 15-H-11,12-EETA, mediate these L-NNA-and indomethacin-resistant vasorelaxations through opening apamin-sensitive K ϩ channels (11,23,42). The studies suggest that THETA and HEETA serve as EDHFs in rabbit aorta.…”
Section: Discussionmentioning
confidence: 90%
“…Using specific inhibitors in rabbit aorta, Singer and Peach (51) first concluded that a LO metabolite mediates the NO-and PG-resistant relaxation to ACh (51). The LO inhibitors cinnamyl-3,4-dihydroxy-␣-cyanocinnamate, nordihydroguaiaretic acid, and ebselen block ACh and AA-induced vasodilation in rabbit aorta (11,39,42). Previous studies in our lab identified the 15-LO metabolites of AA in rabbit aorta.…”
mentioning
confidence: 84%
See 2 more Smart Citations
“…Several substances, including epoxyeicosatrienoic acids, K ϩ , H 2 O 2 , and C-type natriuretic peptide, exhibit EDHF activity (2,4,7,16). In rabbit arteries, we found that EDHF activity is mediated by a 15-lipoxygenase (15-LO) metabolite of arachidonic acid (AA) (3,23). The rabbit endothelium metabolizes AA to 15(S)-hydroperoxyeicosatetraenoic acid [15(S)-HPETE] through 15-LO (23,24,26).…”
mentioning
confidence: 93%